MODERASI PANDEMI COVID-19, TERHADAP HUBUNGAN POLA KERJA DAN WORK LIFE BALANCE DENGAN STRESS KERJA - Puji Ambarukmi; Indarto Indarto; Djoko Santoso (Sekolah Tinggi Ilmu Ekonomi Semarang, 2022)
This study aims to analyze the effect of changes in work patterns on work stress in marketing employees of UOB Bank Semarang Branch, to analyze the effect of work life balance on work stress on marketing employees of UOB Bank Semarang Branch, to analyze the effect of changes in work patterns on work stress with the effect of work life. balance against work stress with the Covid-19 pandemic as a moderating variable. This study uses a sample of 34 marketing people at Bank UOB Semarang Branch, and the data analysis technique is using validity tests, reliability tests, and classical assumption tests, as well as regression tests with moderating variables. Then the t test was also carried out to test the hypothesis, the F test to test the fit of the model and test the coefficient of determination. The test results from this study indicate that the value of the Coefficient of Determination (R2) after moderation is greater than before moderation. This means that the Covid19 pandemic can strengthen the relationship between changes in work patterns and work life balance to work stress.